Between obedient and rebellious: slave women under the female authority. (Buenos Aires, XVIII century) - Gutiérrez Aguilera, María Selina (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The research made for this paper is situated in the city of Buenos Aires during the XVIIIth century. The main objective is to inquire and examine the situation endured by the slave women of the time under the authority of other women, and their connection with the social and legal context of the moment in which they lived. First of all, this portion of the population will be analyzed from a quantitative standpoint, paying attention to diverse demographic characteristics. Afterwards, this social group will be examined in the light of other documents, essentially of legal nature, in which they appear. These women formed a very heterogeneous group with great relevance to scientiic research. Not only did they carry the burden of slavery, they were additionally excluded because of their gender. The cross-reference of of sources, previously referred to above, has permitted an approach to the history of this social group, going deeper into its formation as well as promoting a closer knowledge of its subjects. Certain aspects regarding their daily life are highlighted, conirming the situation of vulnerability in which these slave women lived, but also showing them strong enough to deal with all the problems they had to face because of their condition.